2018
DOI: 10.3390/met8100743
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Properties of Tribological Parameters for Steel Wire Rope under Sliding Contact Conditions

Abstract: Friction and wear seriously affect the safety use of winding hoist wire rope and the damage is a gradual process in practical application. In this paper, the tribological properties of a wire rope under different sliding distances were investigated. The evolutions of the coefficient of friction (COF), temperature rise, and wear characteristics under different contact loads and strokes were analyzed by a series of experiments. The results show that fluctuation of the friction is large in the early stages (befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In the whole test rig, the wire rope positioning mechanism can change the wrapping angle between the test wire rope (15) and the drum (3), the rope is tensioned through the electric push rod (10), and the tension sensor (11) can measure the tensioning force. The double-axis controller can control the lifting of the test wire rope (15) by the stepping motors ( 14) on the lifting platforms (16) to realize the settings of timing and cycle times. Before the test starts, the controller, sensors, and data acquisition equipment should be debugged well, and the motor frequency required for the test should be set.…”
Section: Inter-circle Transition Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the whole test rig, the wire rope positioning mechanism can change the wrapping angle between the test wire rope (15) and the drum (3), the rope is tensioned through the electric push rod (10), and the tension sensor (11) can measure the tensioning force. The double-axis controller can control the lifting of the test wire rope (15) by the stepping motors ( 14) on the lifting platforms (16) to realize the settings of timing and cycle times. Before the test starts, the controller, sensors, and data acquisition equipment should be debugged well, and the motor frequency required for the test should be set.…”
Section: Inter-circle Transition Test Proceduresmentioning
confidence: 99%
“…It is difficult to simulate the contact between steel wires by the tester to truly represent the wires in a wire rope, so it is of great significance to investigate the friction and wear behavior of the wire rope to improve its performance. With the help of a self-made friction and wear tester, Peng et al 14 and Chang et al 15,16 carried out a large number of experimental studies for the two-wire ropes in direct contact under different working conditions. It was found that the wear depth of wire ropes increased linearly with an increase in the contact load, and the major wear mechanisms of wire ropes under the condition of dry friction were abrasive wear, adhesive wear, and fatigue wear.…”
Section: Introductionmentioning
confidence: 99%
“…The sub-assemblies of the KSW-460NE shearer that comes into contact with coal or hard inclusions are subject to wear by dry friction [23][24][25] and shock-generated strain.…”
Section: Introductionmentioning
confidence: 99%
“…The friction and wear of wire ropes seriously threatens the safety and reliability of traction transmission equipment. In order to truly simulate the friction and wear behavior of two wire ropes when they cross contact, Chang et al [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] made a self-made wire rope friction and wear testing machine, and tests with different working conditions, structural parameters, and environmental parameters were carried out. In addition, Peng et al [ 23 ] set up a testing machine to simulate the impact of winding hoisting wire ropes, and found through tests that the increase of load, slip speed, and impact speed seriously threatened the mechanical properties of the wire ropes.…”
Section: Introductionmentioning
confidence: 99%